2010
DOI: 10.1017/cbo9780511760907
|View full text |Cite
|
Sign up to set email alerts
|

Settler Society in the English Leeward Islands, 1670–1776

Abstract: Settler Society in the English Leeward Islands, 1670–1776 is the first study of the history of the federated colony of the Leeward Islands - Antigua, Montserrat, Nevis, and St Kitts - that covers all four islands in the period from their independence from Barbados in 1670 up to the outbreak of the American Revolution, which reshaped the Caribbean. Natalie A. Zacek emphasizes the extent to which the planters of these islands attempted to establish recognizably English societies in tropical islands based on plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Moreover, English inhabitants of the Leeward Islands preferred to divide communities by class rather than by quasi-racial ethnic markers. 40 Kristen Block and Jenny Shaw concur with Zacek about Irish agency in their investigation of this group's complex diplomatic maneuvers in the mid-to-late 17th century. Block and Shaw contend that Irish immigrants to the Caribbean only solidified loyalties to Anglo projects of colonization after proposing numerous schemes of alliance to Spanish and French colonial officials.…”
Section: European Ethnic Minoritiesmentioning
confidence: 98%
“…Moreover, English inhabitants of the Leeward Islands preferred to divide communities by class rather than by quasi-racial ethnic markers. 40 Kristen Block and Jenny Shaw concur with Zacek about Irish agency in their investigation of this group's complex diplomatic maneuvers in the mid-to-late 17th century. Block and Shaw contend that Irish immigrants to the Caribbean only solidified loyalties to Anglo projects of colonization after proposing numerous schemes of alliance to Spanish and French colonial officials.…”
Section: European Ethnic Minoritiesmentioning
confidence: 98%
“…Whilst Karras was sceptical if Scots were able to repatriate wealth from Jamaica, Hamilton endorsed the Williams thesis-apparently the first Scottish historian since Devine to do so (D. Hamilton, 2005). Natalie Zacek confirmed the 'marked tendency' of Scots to secure employment and opportunities for acquaintances and kin helped them overcome modest status in the early English Caribbean settler colonies (Zacek, 2010). Murdoch (2010) also noted the role of Scots as slavers in America.…”
Section: Centring Slavery In Scottish Historiographymentioning
confidence: 99%
“…Among others, Nicholas Beasley has underlined this reality in his study of the rich life of Anglican ritual found in the Caribbean and southern North American colonies. “Puritanism and then revivalism are often seen as the dynamic and democratic American religious tradition as the standards of period evangelicals became the standards of most historians” (Beasley, , p. 14; Kopelson, ; Kupperman, ; Mulcahy, , 166; Zacek, , p. 4–6).…”
mentioning
confidence: 99%